The evaluation of 2568 patients with upper gastrointestinal bleeding - Ali ERGİN,; Kadir AKSÖZ,; Belkıs ÜNSAL,; Günay ÖNDER,; Zakir AKYOL,; Uğur GÖNENÇ,; Nafi YAZICIOĞLU,; Belkıs ÜNSAL,; Himmet KARACA,; Sadun KOŞAY,; Yıldırım SONGÜR,; Bülent KARA,; et al. (Turkish Journal of Gastroenterology, 2020)
-